Changes in sexual identity and substance use during young adulthood. (1st December 2022) - Krueger, Evan A.; Repati, Mykala L.; Harlow, Alyssa F.; Unger, Jennifer B.; Lee, Jungeun Olivia; Pedersen, Eric R.; Conn, Bridgid M.; Wong, Carolyn; Young, Lindsay E.; Barrington-Trimis, Jessica L.; Leventhal, Adam M.
Abstract: Background: Sexual identity is dynamic, and changes in identity (e.g., from heterosexual to lesbian, gay, bisexual, or queer [LGBQ+]) are common during young adulthood. It is not well-understood how sexual identity changes may be associated with substance use risk. Methods: Two waves of data (baseline: October, 2018–October, 2019; follow-up: May–October, 2020) were used from a prospective cohort of young adults (N = 1896; mean age=21.2). Frequency of past 30-day use and new initiation of five substance use outcomes (alcohol, any tobacco, e-cigarettes, cannabis, illicit drugs) were compared across four groups: consistently heterosexual (N = 1567), consistently LGBQ+ (N = 244), heterosexual to LGBQ+ (N = 65), and LGBQ+ to heterosexual (N = 20). Results: Consistently LGBQ+ (vs. consistently heterosexual) participants reported greater frequency of past 30-day use of alcohol (aOR=1.34, 95% CI=1.04–1.72), any tobacco products (aOR=1.88, CI=1.34–2.63), e-cigarettes (aOR=1.49, CI=1.01–2.19), cannabis (aOR=1.36, CI=1.01–1.84), and illicit drugs (aOR=2.84, CI=1.77–4.56). Heterosexual to LGBQ+ (vs. consistently heterosexual) participants reported greater frequency of past 30-day use of any tobacco products (aOR=1.87, CI=1.06–3.33) and illicit drugs (aOR=2.48, CI=1.10–5.62), and had greater risk of initiating alcohol (aRR=1.82, CI=1.02–3.25) and cannabis use (aRR=2.90, CI=1.81–4.64). LGBQ+ to heterosexual (vs. consistently LGBQ+) participants reported lower frequency of past 30-day use of alcohol (aOR=0.35, CI=0.14–0.88) and any tobacco products (aOR=0.15, CI=0.03–0.80). Conclusions: Identifying as LGBQ+ was associated with increased risk for frequent substance use, and newly adopting an LGBQ+ identity was associated with increased risk for new substance use initiation. Prevention and treatment interventions may need to tailor messaging to young people who have newly adopted an LGBQ+ identity. Highlights: LGBQ+ identity was associated with increased substance use prevalence and frequency. Nearly 5% of the sample changed sexual identities over the course of one year. Adopting a heterosexual identity was associated with decreased risk for frequent use. Adopting an LGBQ+ identity was associated with increased risk for initiating use.